The influence of 3D printing mode on the chemical composition and structure of 30HGSA steel - Yury G. Kabaldin; Maksim S. Anosov; Yuliya S. Mordovina; Mikhail A. Chernigin (Frontier Materials & Technologies)
The authors carried out the study of the influence of 3D printing modes on the structure and chemical composition of 30HGSA steel (chromansil) samples produced by the method of additive electric arc surfacing. To study the influence of the electric arc surfacing mode on the chemical composition of the steel under study, an optical emission analysis of the samples was carried out. The influence of the surfacing mode on the resulting structure was assessed over the entire height of the deposited walls at magnifications of ×50, ×100, ×200 and ×500. Optical emission analysis identified a change in the material chemical composition associated with the loss of chemical elements. It was found that the degree of loss of C, Cr and Si increases almost linearly and is directly proportional to the surfacing heat input (Q, J/mm). The exact influence of an increase in the surfacing heat input on the Mn content was not found, but a relationship between the degree of its loss and the voltage (U, V) during surfacing of samples was identified. Microstructural studies of all samples did not reveal a large number of systemically formed structural defects characteristic of cast and welded products (pores, shrinkage cavities, etc.), which confirms the high quality of the metal in goods produced by electric arc surfacing. Analysis of micrographs taken in different areas of the samples allowed determining that the metal microstructure does not undergo significant changes under different surfacing modes; the main tendencies in changes in the structure along the height of the sample are preserved. All samples demonstrated the formation of a highly dispersed structure, regardless of the 3D printing parameters. The most favorable metal structure, suitable for subsequent use in the production of goods using additive manufacturing, was recognized as the structure of the sample deposited using mode No. 5 (I=160 A, U=24 V, Q=921.6 J/mm). This mode can be used for further study of the problems of additive electric arc surfacing of 30HGSA steel.